PENGUATAN EKSISTENSI SAPI BALI MELALUI PENDEKATAN IPTEKS DAN BERORIENTASI WISATA PEDESAAN DI DESA SOBANGAN KECAMATAN MENGWI KAB. BADUNG - Sumiyati, Sumiyati; Miwada, IN.S.; Kebayantini, N.L.N. (Buletin Udayana Mengabdi, 2017)
The objective of the service is the call for support for the strengthening of the existence of Bali cattle in the village Sobangan as assets through an approach of science and technology and have the potential to support educational tour of Bali cattle. The method of implementation of these activities through education and training to strengthen the existence of Bali cow to cow potential introduction bali by establishing a center of attraction educational tour of Bali cattle. The results show that the activities of Bali cattle population in this village of more than 600 tail and strengthening of existence through the feed management has been done. Formulation waste utilization as silage hay and forage provision of counseling throughout the year with the adoption of methods of STS have been able to encourage the increase (over 85%) of farmers knowledge. Existence of Bali cattle in the village this Sobangan had driven through the establishment of an alternative travel package in the form of educational tourist attraction of Bali cattle and received a positive response from the community. Conclusion activities that efforts to strengthen the existence of Bali cattle through feed management training and the establishment of educational tourist attraction of Bali cattle have been able to increase community to preserve Bali cattle as a potential asset.